Cardioprotective Role of Colchicine Against Inflammatory Injury in a Rat Model of Acute Myocardial Infarction. (September 2018) - Bakhta, Oussama; Blanchard, Simon; Guihot, Anne-Laure; Tamareille, Sophie; Mirebeau-Prunier, Delphine; Jeannin, Pascale; Prunier, Fabrice
Background: Inflammation plays a crucial role in the pathophysiology of myocardial ischemia/reperfusion (I/R) injury. A clinical trial has recently reported a smaller infarct size in a cohort of patients with ST-segment elevation myocardial infarction (MI) treated with a short colchicine course. The mechanism underlying colchicine-induced cardioprotection in the early MI phase remains unclear. We hypothesized that a short pretreatment with colchicine could induce acute beneficial effects by protecting the heart against inflammation in myocardial I/R injury. Methods and Results: Rats were subjected to 40-minute left anterior descending coronary occlusion, followed by 120-minute reperfusion. Colchicine (0.3 mg/kg) or a vehicle was administered per os 24 hours and immediately before surgery. Infarct size was significantly reduced in the colchicine group (35.6% ± 3.0% vs 46.6% ± 3.3%, P < .05). The beneficial effects of colchicine were associated with an increased systemic interleukin-10 (IL-10) level and decreased cardiac transforming growth factor-β level. Interleukin-1β was found to increase in a "time of reperfusion"-dependent manner. Colchicine inhibited messenger RNA expression of caspase-1 and pro-IL-18. Interleukin-1β injected 10 minutes prior to myocardial ischemia induced greater infarct size (58.0% ± 2.0%, P < .05) as compared to the vehicle. Colchicine combined to IL-1β injection significantly decreased infarct size (47.1% ± 2.2%, P < .05) as compared to IL-1β alone, while colchicine alone exhibited a significantly more marked cardioprotective effect than the colchicine-IL-1β association. Conclusion: The cardioprotection induced by a short colchicine pretreatment was associated with an anti-inflammatory effect in the early reperfusion phase in our rat MI model.